Can Discount Window stigma be cured? An experimental investigation - Olivier Armantier; Charles A. Holt (Federal Reserve Bank of New York, 2024)
A core responsibility of a central bank is to ensure financial stability by acting as the "lender of last resort" through its Discount Window. The Discount Window, however, has not been effective because its usage is stigmatized. In this paper, we study experimentally how such stigma can be cured. We find that, once a Discount Window facility is stigmatized, removing stigma is difficult. This result is consistent with the Federal Reserve's experiences which have been unsuccessful at removing the stigma associated with its Discount Window.
Keywords: E58; G01; C92; 330; lender of last resort; discount window; stigma; laboratory experiment